Medieval Polities and Modern Mentalities. - Reuter, Timothy (Cambridge University Press, 2006)
Timothy Reuter was a perceptive and original thinker, a medievalist with extraordinary range. This collection of his essays addresses three themes: historiography and the development of the modern study of the medieval past; the importance of symbolic action and communication; and the need to avoid anachronism in considering medieval politics.